Monitoring of Lactic Acid Fermentation Process Using Fourier Transform near Infrared Spectroscopy. Issue 5 (October 2013) - Grassi, Silvia; Alamprese, Cristina; Bono, Veronica; Picozzi, Claudia; Foschino, Roberto; Casiraghi, Ernestina
The aim of this paper was to evaluate the suitability of Fourier transform near infrared (FT-NIR) spectroscopy, combined with multivariate data analysis, to monitor milk lactic acid fermentation as an indication of possible deviations in quality parameters. Fermentation trials performed with different inocula ( Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus as single or in mixed cultures) at three incubation temperatures (37°C, 41°C and 45°C) were monitored by FT-NIR spectroscopy. Rheological and conventional quality parameters (microbial counts, pH, titratable acidity, lactose, galactose and lactic acid concentrations) were used as reference values to assess the findings with FT-NIR spectroscopy. Principal component analysis was applied to spectra to uncover molecular modifications. PC1 scores, rheological data and conventional quality parameter values were modelled as a function of fermentation time to designate critical points all along the process. Results showed that FT-NIR spectroscopy is a useful tool for real-time assessment of curd development during fermentation, offering crucial information in agreement with rheology and conventional quality parameters.